Optimum birth interval (36–48 months) may reduce the risk of undernutrition in children: A meta-analysis - Ntambara, James; Zhang, Wendi; Qiu, Anni; Cheng, Zhounan; Chu, Minjie (Frontiers in Nutrition, 2023)
Abstract: Background: Although some studies have highlighted short birth interval as a risk factor for adverse child nutrition outcomes, the question of whether and to what extent long birth interval affects better nutritional outcomes in children remains unclear. Methods: In this quantitative meta-analysis, we evaluate the relationship between different birth interval groups and child nutrition outcomes, including underweight, wasting, and stunting. Results: Forty-six studies with a total of 898,860 children were included in the study. Compared with short birth interval of < 24 months, birth interval > 24 months and risk of underweight showed a U-shape that the optimum birth interval group of 36-48 months yielded the most protective effect (OR = 0.54, 95% CI = 0.32-0.89). Moreover, birth interval > 24 months was significantly associated with decreased risk of stunting (OR = 0.61, 95% CI = 0.55-0.67) and wasting (OR = 0.63, 95%CI = 0.50-0.79) when compared with the birth interval < 24 months. Conclusion: The findings of this study show that longer birth intervals (> 24 months) are significantly associated with decreased risk of childhood undernutrition and that an optimum birth interval of 36-48 months might be appropriate to reduce the prevalence of poor nutritional outcomes in children, especially underweight. This information would be useful to government policymakers and development partners in maternal and child health programs, especially those involved in family planning and childhood nutritional programs.